Association of near-infrared spectroscopy-defined lipid rich plaque with lesion morphology and peri-coronary inflammation on computed tomography angiography. (April 2022) - Yamaguchi, Masao; Hoshino, Masahiro; Sugiyama, Tomoyo; Kanaji, Yoshihisa; Nagamine, Tatsuhiro; Misawa, Toru; Hada, Masahiro; Araki, Makoto; Hamaya, Rikuta; Usui, Eisuke; Murai, Tadashi; Lee, Tetsumin; et al.
Abstract: Background and aims: Recent studies have reported that the lipid-rich plaque (LRP) detected by near-infrared spectroscopy (NIRS) and the pericoronary adipose tissue attenuation (PCATA) evaluated by coronary computed tomography angiography (CCTA) are associated with worse outcomes. We sought to investigate the relationship between NIRS-defined LRP and PCATA or the incremental ability of PCATA for the prediction of the presence of NIRS-defined LRP when added to the CCTA-derived morphometric findings. Methods: A total of 101 de novo lesions of 101 patients with chronic coronary syndromes (CCS), who underwent pre-procedural CCTA and NIRS during percutaneous coronary intervention (PCI), were retrospectively studied. PCATA was assessed by the crude analysis of the mean CT attenuation value of the culprit vessel. NIRS-defined LRP was defined as a maximum lipid core burden index in 4 mm ≥ 400. Univariate and multivariate logistic regression analyses were performed to determine the predictors of NIRS-defined LRP. Results: NIRS-defined LRP was observed in 37 patients and median PCATA was −72.71. A significant relationship was observed between LCBI and PCATA (r = 0.24, p = 0.001). PCATA (OR: 4.99; 95% CI: 1.48–16.82; p = 0.010) and CCTA-derived positive remodeling (OR: 12.53; 95% CI: 3.56–44.07; p < 0.001) were independent predictors of NIRS-defined LRP. Net reclassification and integrated discrimination improvement indices were both significantly improved when PCATA was added to the reference model including clinical characteristics and CCTA-derived morphometric findings. Conclusions: Comprehensive assessment of CCTA including PCATA may provide reliable information to identify the presence of NIRS-defined LRP potentially leading to future adverse events after PCI. Graphical abstract: Image 1 Highlights: Pericoronary adipose tissue attenuation may provide reliable informations.